Effect of Tabata Training Program in Improving Maximal Oxygen Consumption among College Women Kabaddi Players - Ilavarasi, L.; Chandrasekaran, K.; Ramesh, C. (Journal of Neonatal Surgery, 2025)
The study aimed to experiment the effect of tabata training on maximal oxygen consumption among college women kabaddi players. The experimental group was divided into two subgroups after the initial screening for selection criteria, such as tabata training, and the control group, which was not subjected to any experimental training other than their ordinary everyday activities. In this study, college women kabaddi players in the Madurai Kamarajar University affiliated colleges were tested using a pretest and posttest design, as well as a control group. A total of 30 kabaddi players who represented their college team were enlisted and divided into two groups: experiment [15 players] and control [15 players]. The level of vo2 max in both groups was assessed and documented using the Beep Test. ANCOVA with a post-hoc test was used. The threshold of significance 0.05 was chosen to examine the acquired results on variables and was deemed sufficient for the investigation. In conclusion, tabata training is an effective method for enhancing college women kabaddi players’ VO2 max.